Argumentación jurídica sobre el despido ineficaz a los dirigentes sindicales vs estabilidad laboral en el gobierno autónomo descentralizado del cantón Pastaza - Villacreses Cando, Helen Mishell (2024)
ABSTRACT In our country the right to work is one of the main principles that our Constitution has the obligation to protect and guarantee its strict compliance since work is an activity that dignifies, a source of satisfaction, and the personal and professional fulfillment of any person. It promulgates and strengthens the labor rights of Ecuadorian workers when they have been violated; because, in labor regulations, current reforms guarantee the compliance of these rights which are inalienable and intangible. Currently, the legal concept of ineffective dismissal is established in the new regulations that norm the current Labor Code whose objective is to grant a protection measurement or legal protection to some workers that are considered vulnerable guaranteeing labor stability, especially for female workers who are pregnant or who are associated to their maternity condition as well as those who assume the role of union leaders by allowing them to reinstate to their work positions if they had been fired untimely by the employers. Different organizations that protect the right to work have assured that there is total lack of compliance in regards to the protection of labor rights of workers, especially those untimely dismissal against the union leaders because if they count on laws that protect them there are regulations and legal problems for applying them due to constant lack of respect that the employers commit against them; this has led to labor conflicts where the ineffective dismissal figure protects them from this arbitrariness that put its continuity and labor stability within their work place into risk. Within this research work, the topic regarding the ineffective dismissal is founded as well as the constant violations and persecutions that union leaders have suffered when exercising their functions that have not been accomplished properly since what is established in the Constitution, the Labor Code and unionism orders have not been respected.